Analysis of The Effect of The Intake Manifold Curvature Angle of The KZR Engine on The Characteristic of Air Fluid Flow - Arga Fernando; Rizqi Fitri Naryanto; Ahmad Roziqin; Sonika Maulana (Universitas Negeri Semarang, 2026)
This research is to determine the effect of variations in the intake manifold curvature angle on turbulence intensity, turbulent kinetic energy, flow velocity, and fluid flow patterns. One effort to reduce excessive fossil fuel consumption is modifying vehicles to consume fuel more efficiently through a more complete combustion process. One such method involves modifying the intake manifold of a motorized vehicle. This study used FD-based numerical study with a quantitative approach to investigate changes in the curvature angle of the intake manifold. The aim of The modification process of the intake manifold structure was conducted on a 2012 Vario 125 (KZR) motorcycle through simulation. The purpose of this simulation is to conduct a fundamental analysis before implementing changes to the intake manifold structure. The geometric definition of the intake manifold was created using SolidWorks 2020, and the simulation was performed using Ansys Workbench 2022. The curvature angle variations of the intake manifold were 110°, 120° (standard), and 130°. The simulation results showed differences in outcomes for each curvature angle. The highest turbulence intensity, turbulent kinetic energy, and flow velocity were observed at the 110° angle. This indicates that modifying the intake manifold through simulation can influence turbulence flow during the combustion process. These findings can be considered to achieve better torque and power output in vehicles in the future.